Application of UAV in Visual Inpection for Civil Infrastructure at Sekolah Menengah Kebangsaan Bandar Maharani, Muar - Rosli, Nor Shuhada Natasha; Mohd Akbar, Nur Adlin Sabrina; Kamarolzaman, Nurul Qamarina; Ahmad Hakimi Mat Nor; Masiri Kaamin (Multidisciplinary Applied Research and Innovation, 2024)
Building inspection is important to understand the building condition or defect index. Traditional methods of building inspection are too risky, expensive and time-consuming such as the use of scaffolding and ropes which result in inaccurate data, the use of drones helps produce accurate data and reduce risk. This study aims to produce othomosaic images using Pix4D Mapper software, classify building defects using Public Works Department Standards (JKR Standard) and analyze building damage using Unmanned Aerial Vehicle (UAV). The UAV is the main tool used in the high-rise inspection study to generate data through the Pix4d Mapper software, and the images are then analyzed using JKR Standard methods. Building inspections using UAVs with the JKR method can determine the location, type, and level of defects in the building. The use of UAVs allows damage and defects in building structures to be detected closely and quickly even at high altitudes and the use of cameras is also used in low areas.